Um estudo da contribuição de livros didáticos de matemática no processo de disciplinarização da matemática escolar do colégio 1943 a 1961 - Ribeiro, Denise Franco Capello (2011)
This research has as objective the study of the historic way of the Mathematics scholar subject constitution to High School, at Gustavo Capanema Reform, time in which was made the reorganization of the Mathematics teachings to this teaching level and the rising of the Mathematic didactic books collection entitled Matemática 2º Ciclo , to the 1st, 2nd and 3rd grades, edited to assist the new Mathematics syllabus of these courses, by the authors Euclides Roxo, Roberto Peixoto, Haroldo Lisbôa da Cunha and Cesar Dacorso Netto, also known as the 4 authors Collection. This collection standardizes the structure of other Mathematics didactic collections books contributing to the teaching standardization and the Mathematics scholar subject constitution. This investigation uses mainly the theoric basis of André Chervel, Alain Choppin and Roger Chartier, the legislation related to this Reform and Mathematic didactic books edited to High School courses, whose authors were consulted by High School students (Classic and Scientific), in the scholar library of the current Sao Paulo State School, in the period between 1943 to 1961, as mainly research sources. The main question of this investigation is: How the Mathematics didactic books from the collection entitled Matemática 2º Ciclo , by Euclides Roxo, Roberto Peixoto, Haroldo Lisbôa da Cunha and Cesar Dacorso Netto, as known as the 4 authors Collection, written to High School courses, in the Capanema Reform period, contributed to the Mathematic scholar subject constitution, to this teaching level? This research seeks to give a contribution to the History of Scholar Mathematics and to the Mathematic Education in Brazil